From Physical Puberty to Intellectual Maturity: Comparative Analysis of Maturity Presumption in Iranian, French and Islamic Law - Mahmoud Kazemi; Abbas Borzouei (Faṣlnāmah-i Pizhūhish-i Huqūq-i Khuṣūṣī, 2016)
In Iranian Civil Law. like in Islamic Jurisprudence, in addition to puberty, the maturity is necessary in order to have capacity for carrying out transaction. The age of puberty is defined in jurisprudence; however,  there is no specific age of maturity. Before the revolution in Iran , Article 1210 of the Civil Code determined the age of 18 as a criterion for maturity. After the Islamic Revolution, this provision changed under the pretext of conformity of the Civil Code with Islamic Jurisprudence.  The text of this provision regards the age of puberty as maturity. However, according to note 2,  when the maturity can be proved, it is possible to give him his properties. This conflict has led to debate and controversy. In this paper, the" maturity "is considered from jurisprudence perspective and it is concluded: First, the maturity is merely necessary for the possession of financial affairs. Second, there is no consistency between amendments made to Art 1210 and the view of majority in Islamic jurisprudence. Jurists do not accept the"puberty" as a presumption of maturity. Third ,the maturity is a common concept and it can be proved conventionally. For the purpose of proving it , there is no need for the decision of court